Pengaruh Beban Kerja dan Komunikasi Internal terhadap Produktivitas Kerja Pegawai Dinas Sosial Kota Depok - Nabila Rahma Syafira (Maeswara : Jurnal Riset Ilmu Manajemen dan Kewirausahaan, 2025)
The Depok City Social Service is a local government agency with important responsibilities in providing various social services for the community, including services for vulnerable groups, social empowerment, and handling welfare issues. Employee performance in this agency is a key factor in the successful implementation of planned programs. This study aims to analyze the effect of workload and internal communication on the work productivity of Depok City Social Service employees. The study used a quantitative approach with 34 respondents, where the entire population was sampled through a saturated sampling technique. Data were collected using a Likert-scale questionnaire instrument, designed to measure employee perceptions regarding the level of workload, the effectiveness of internal communication, and the level of work productivity. The results of the analysis show that the workload variable (X1) has a positive and significant effect on work productivity (Y), as evidenced by the calculated t value of 4.235, which is greater than the t table of 1.695, and a significance level of 0.000 <0.05. These findings indicate that proper workload management can encourage increased employee productivity. The internal communication variable (X2) was also proven to have a positive and significant influence on work productivity, with a calculated t of 2.332 > ttable 1.695 and a significance value of 0.026 < 0.05, which confirms the importance of effective information flow and coordination in the work environment. Simultaneously, workload and internal communication have a significant influence on employee work productivity, with an Fcount value of 41.065 greater than the Ftable of 3.29 at a significance level of 0.000 < 0.05. The coefficient of determination (R²) value of 0.726 indicates that the two variables together are able to explain 72.6% of the variation in employee work productivity, while the remaining 27.4% is influenced by other factors not examined in this study.